BUDGETARY POLICY IN THE EUROPEAN UNION UNDER GEOECONOMIC UNCERTAINTY: TRENDS, CHALLENGES, AND THE 2024 REFORM OF THE STABILITY AND GROWTH PACT - Yakubovskiy , S. O. (The actual problems of regional economy development, 2025)
The article explores the evolution and transformation of budgetary policy in the European Union (EU) in the context of growing geoeconomic uncertainty, with a particular focus on the period from 2013 to 2024. The research is motivated by two major external shocks – the COVID-19 pandemic and Russia’s full-scale war against Ukraine – which have revealed significant weaknesses in the EU’s pre-existing fiscal governance framework and necessitated a comprehensive revision of the Stability and Growth Pact (SGP). The study addresses how these crises exposed asymmetries in fiscal responses and capacities across member states, leading to divergent recovery trajectories and highlighting structural imbalances in the Union's fiscal architecture. The primary objective of this study is to assess the effectiveness of the reformed SGP, adopted in 2024, in promoting a more adaptable, resilient, and sustainable fiscal model while maintaining macroeconomic discipline. The research methodology is based on comparative analysis, combining empirical data on budget deficits with critical assessments of EU legal documents and scholarly literature. Fiscal dynamics are evaluated across a sample of EU countries characterized by either strong fiscal performance (e.g., Denmark, Ireland, Luxembourg) or persistent deficits and weak fiscal governance (e.g., Romania, France, Hungary, Poland). The findings demonstrate that the 2024 reform introduces more flexible, country-specific adjustment paths, supported by medium-term fiscal planning, the creation of fiscal buffers, and incentives for structural reforms and public investment. However, the study also identifies several critical weaknesses – most notably, the subjectivity of the Debt Sustainability Analysis (DSA), the political nature of enforcement mechanisms, and the ongoing risk of fiscal slippage. The scientific novelty of this research lies in its systematic assessment of the revised SGP as a response to overlapping crises and its contribution to the broader academic discourse on supranational fiscal integration. The study offers both theoretical insights into institutional adaptation under stress and practical implications for EU-level coordination, enforcement credibility, and national fiscal strategy design.